Antegrade thoracic endovascular aortic repair using an ascending aortofemoral through-and-through wire technique for a severely tortuous aorta associated with rickets - Morishita, Atsushi (Surg Case Rep, 2017)
BACKGROUND: Severe aortic tortuosity of the access route often prevents successful complete exclusion of an aneurysm in thoracic endovascular aortic repair (TEVAR). CASE PRESENTATION: We performed antegrade TEVAR on a 79-year-old man with right hemiparesis. We deployed the stent graft from the ascending aorta with a tube graft conduit to treat a descending thoracic aortic aneurysm associated with rickets and multiple comorbidities. Although the application of a ministernotomy diminished the potential advantages of endovascular treatment in view of less invasive surgery, antegrade TEVAR using an ascending aortofemoral through-and-through wire technique was a good option in this patient because a conventional retrograde approach was not feasible due to his severely tortuous aorta. CONCLUSIONS: To avoid device-related complications, it is crucial to make a prudent preoperative decision on a patient-by-patient basis, taking into account the appropriate access site, adjuvant guidewire technique, and adjunctive surgical interventions.